2018
DOI: 10.1556/2006.7.2018.17
|View full text |Cite
|
Sign up to set email alerts
|

Does the uptake of wagering inducements predict impulse betting on sport?

Abstract: Background and aimsMarketing inducements for addictive products, such as wagering, can prompt impulse purchasing by triggering consumption reminders, urges, and cravings. Wagering inducements incentivize betting by providing bonus bets, money-back guarantees, deposits into betting accounts, and discounts. Their promotion during sporting events, push marketing efforts directed at consumers, and ease of uptake at the point-of-sale, may trigger betting on impulse. This study examined whether the uptake of wagerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 47 publications
3
46
0
Order By: Relevance
“…It could be the case that warning labels and education campaigns are an insufficient intervention to debias consumers about the complex statistical information underlying modern soccer bets (Weiss-Cohen et al, 2018) and given the messages in gambling marketing prompting more frequent and riskier gambling (Hing et al, 2018(Hing et al, , 2019. This may particularly be the case in soccer betting, given evidence that sports fans are prone to wishful thinking (Babad, 1987) and are overconfident even when the financial stakes are high (Simmons & Massey, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It could be the case that warning labels and education campaigns are an insufficient intervention to debias consumers about the complex statistical information underlying modern soccer bets (Weiss-Cohen et al, 2018) and given the messages in gambling marketing prompting more frequent and riskier gambling (Hing et al, 2018(Hing et al, , 2019. This may particularly be the case in soccer betting, given evidence that sports fans are prone to wishful thinking (Babad, 1987) and are overconfident even when the financial stakes are high (Simmons & Massey, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Wagering inducements "incentivise both race and sports betting through offers including sign-up and referral bonuses, 'free' bets, matching deposits, cash refunds, bonus odds, happy hours and mobile betting bonuses" [63] (p.686). One study documented the features of inducements [63] and the other involved a survey with 1813 sports bettors to explore whether the uptake of wagering inducements predicted impulse betting, finding this was the case among problem gamblers and frequent sports viewers [64].…”
Section: Advertising and Inducementsmentioning
confidence: 99%
“…A Norwegian study showed that problem gamblers were more likely to be aware of gambling marketing and to report that it increased their involvement in gambling [48]. Australian sports bettors, and in particular problem gamblers, who report taking advantage of advertised financial incentives appear to place more impulsive bets [49]. Problem gamblers in Norway also appear to be exposed to more gambling adverts than non-problem gamblers on social media [50].…”
Section: Gambling Marketing's Effect On Behaviourmentioning
confidence: 99%